Increasing inequality and financial instability - Peter Skott (University of Massachusetts, Department of Economics, 2011)
Rising inequality affects the composition of asset demands as well as aggregate demand. The poor have few financial assets and their portfolio is skewed towards fixed-income assets. The rich, by contrast, hold a large proportion of their wealth in stocks. Thus, an increase in inequality tends to raise the demand for stocks. This generates capital gains, and these gains can fuel a bubble, as desired portfolios shift further towards stocks.
Keywords: E11; E21; 330; earnings inequality; portfolio composition; financial instability